Factors influencing parents’ food-purchasing decisions in the Pacific: a qualitative study in Tonga - Sela Ki Folau Fusi; Alessandro Crocetti; Adrian J. Cameron; Megan Ferguson; Kathryn Backholer; Jennifer Browne (BMC Public Health)
Abstract Background An unhealthy diet is the leading preventable risk factor for the development of diet-related non-communicable diseases, and the food environment is considered a major determinant of dietary intake. Food-purchasing decisions in retail settings are influenced by a range of individual, environmental, and interpersonal factors. The aim of this study was to explore the perceived influences on food-purchasing decisions among Tongan parents. Methods This qualitative study involved semi-structured interviews in 2023 with 21 Tongan parents aged 27 to 51 years in Tongatapu, Tonga, a Pacific Island country. Parents were asked questions about the factors that determine where they do their grocery shopping and what influences their food-purchasing decisions. Interview transcripts were analysed using reflexive thematic analysis, informed by the socio-ecological model of food and beverage intake. Results Four themes were constructed from the interview data across the different levels of the socio-ecological model of food and beverage intake, each of which represented parents’ perceived influences on how they purchased foods from retail outlets. At the micro level, we found that parents often struggle to prioritise healthy food when balancing financial and time constraints, as well as family and cultural expectations regarding food provision. At the meso level, we found that food availability in local retail outlets was important, while at the macro level, the cost of healthy food relative to unhealthy food was a key factor driving purchasing decisions. Conclusions Health promotion efforts and public health policies should recognize the multi-dimensional nature of the factors influencing Tongan parents’ food-purchasing decisions. Given the prevalence of diet-related non-communicable diseases in Tonga, the social, cultural, commercial and environmental factors driving unhealthy food-purchasing and population diets in Tonga should be a priority for governments and health promotion practitioners.